Electrochemical Glucose Quantification as a Strategy for Ethanolic Fermentation Monitoring (2019)
ABSTRACT: The possibility of using an electrochemical biosensor, using screen-printed electrodes modified with a carbonaceous material and a commercial kit for the determination of glucose, to monitor an ethanolic fermentation was analyzed. The determination is based on the electrochemical oxidation reaction of NADH that occurs at a potential where the components of the kit do not generate a current signal, even in the presence of the fermentation medium. The electrochemical system was used to analyze the variation of glucose concentration during a laboratory-scale fermentation. The results were contrasted with the variation of standard characterization parameters such as pH, total soluble solids (TSS), the viability of the yeast, and concentration of ethanol produced. Of these values, the total soluble solids should be related to the concentration of glucose obtained by the electrochemical sensor, however, this last measure is more specific for sugar since the TSS refers to all soluble solids. The obtained results allow us to verify the usefulness of the electrochemical method for real-time monitoring of a fermentation.